EP.WE.20At a glance: the impact of COVID-19 on Emergency General Surgery. (28th October 2021) - Aboul-Enein, Mohamed; Ishak, Peter; Bhambra, Maninder; Ricart, Pol; Ishak, Lisa; Perry, Anthony
Abstract: Aim: This study investigated the impact of COVID-19 on emergency general surgery practice, in a district general hospital in the United Kingdom, particularly on referrals, diagnosis, investigations, management pathways, outcomes, patient behaviour and consultant practice. Methods: Retrospective data collection from two cohorts: 112 patients admitted over one week in pre-COVID period and 90 patients admitted over one week during the COVID period. We used patient questionnaire and a consultant questionnaire to collect data on patient behaviour and consultant practice. Results: Almost four times and seven times increase in performed X-rays (CXRs)and CT-thorax-abdomen-pelvis (TAPs) respectively. The COVID period saw 6.5% increase in conservative and 6.2% reduction in surgical management, and about 50% decline in length of stay (LoS) in conservatively managed patients. 71% of patients' decisions to attend hospital were not affected and 78.6% of consultant surgeons preferred to manage patients conservatively during the COVID period. Conclusion: Overall, there were delayed patients' presentations to hospital at almost twice, increase in paediatric referrals, a surge in performed scans, and a reduction in hospital stay in patients who were managed conservatively. Patient behaviour to attend hospital was not heavily influenced by COVID, but consultant practice certainly changed towards more conservative choices. Future studies should explore the impact on paediatric referrals and long-term effects on surgical training. This study's manuscript has been accepted for publication in the Surgical Practice Journal.